Alfalfa Certified Seed Production - Ajir, Gulmohammad (Journal of Natural Sciences – Kabul University, 2025)
There are several differences between alfalfa produced for forage and alfalfa produced for seed, with two major distinctions being water usage and plant density. Alfalfa seed production requires about half or less of the water needed for forage production. For alfalfa hay production, growers typically plant between 16–18 kg of seed per hectare, whereas for seed production, 12–15 kg of seed per hectare is used. Alfalfa grown for seed requires an arid and dry climate. Fertile soil is beneficial, but alfalfa can grow in a variety of soil types. Alfalfa seed production would be nearly impossible without bees, and most alfalfa seed producers rely on bees in seed production areas. There are also some pests that growers may need to monitor.